Beneficiamento e comercialização dos produtos dos sistemas agroflorestais na Amazônia, Comunidade Santa Luzia, Tomé - Açu, Pará - COUTO, Maria Cristina de Moraes (Universidade Federal do Pará, 2021)
In Santa Luzia community, in the municipality of Tomé-Açu, as in the Northeast Pará, there is nowadays a process of change among crops, involving slash and burn systems in the pasture establishment or subsistence crops, for the implementation of agroforestry systems, as a way to diversify production and get better income and new ways to market their organic products. As the marketing and processing of production are considered obstacles in family farming, this research identifies and analyzes the importance of the organization in these processes in Santa Luzia community through the characterization of the association, describing and evaluating the processing and the marketing of the household production, determining the economic, social and environmental changes in the community to add value to the products of agroforestry systems. Visits were conducted with questionnaires to all members of the association, forming a sample of 21 production units, allowing a socio-economic study on the family units, in addition to using descriptive statistical methods and multivariate statistics through factorial analysis and Cluster Analysis, which allowed us to evaluate the size of the data in relation to the variables that determine the agroforestry systems and the marketing process. The results indicate that 95% of the families interviewed have agroforestry systems with a large crops diversification and 95% perform some kind of processing in their products (71% of the production),which provided new market opportunities and better prices, obtaining an average annual revenue of R$ 22.241,35, ensuring them, better economic and social conditions, which allows us to conclude that the organization and production agroindustrialization promoted better marketing and higher production income in the community of Santa Luzia.